Getting it all done (HBR working parents series., 2021)
"Stop juggling; start managing everything you need to do at home and at work. It used to be simple: Stay late, turn in flawless work, catch up on sleep later. You needed that mind-set to get where you are, but that's not going to cut it anymore. You need to make different choices to succeed at work, as a parent, and as a family member. Getting Things Done at Home and Work can't teach you how to be in two places at once, but it provides you with expert advice as you manage the challenge of succeeding at work while making sure your family is housed, fed, healthy, safe, and educated. You'll learn to: set up schedules and routines that work, spend your time and energy on the most valuable activities, set reasonable expectations and limits in the always-on culture, keep exercising your management skills once you've left the office, move on with resilience when you occasionally drop the ball. embody the work and life values you believe in for your children"--